A systematic methodology toward creating spatial quality in urban settings - Thomas, Derek Charles (Environmental Humanities, 2023)
Urban settings, conceived and implemented in the climate of modern-day urbanisation and technology, show undesirable trends. In the typical situation, due to the absence of the urban dweller's participation in the planning and design process, prescriptive decision-making directs and shapes the urban environment on the basis of the objectives of the trained professional or a developer. The disciplines of architecture, urban design, and urban planning, well endowed with research in terms of their philosophical, cultural, and historical dimensions, traditionally overlook systematic and impartial methods in realisation of design objectives. In addition, architects generally focus within the confines of the immediate site, ignoring the wider context. Urban planners and designers tend to follow their perceptions of the urban setting and pragmatic objectives, and to overlook the elements which constitute spatial quality for others. Planning and design tasks performed in this way are prescriptive and perfunctory, and do not meet the urban dweller's perceptions of spatial quality. Although the planning and design disciplines can avail themselves of considerable intellectual resources, systematic methods to synthesise both the subjective opinion of the urban dweller and expert opinion of specialists are lacking. With current global scenarios, the need to develop methods for participation becomes even more relevant and urgent. The likelihood of high-density settings is ominous without changes in planning and design approaches. The overall objective of this thesis is to develop a methodology which meets the demands of the situations described. The data for this study are derived from a theoretical examination of the attributes which contribute to the perceptions of spatial quality in the urban setting. A thematic analysis, carried out against the background of factors, such as spatial patterning, links social well-being with characteristics of the urban environment. Consistent and invariant spatial quality indicators are derived which are then associated with spatial performance. A spatial frame is then identified to structure the methodology into recognisable and manageable urban spatial components. Expectations of spatial performance are translated systematically into primary planning and design generators to complete the elements of the methodology. The problem of how to involve urban dwellers and specialist designers and planners for a consensus useful in the planning process is examined. The comprehensive methodology developed by Sondheim for assessing environmental impacts incorporates the necessary features for adaptation to new urban settings and resolves the problem of polling divergent priorities without requiring discussion or consensus amongst participants. The matrix procedures of the chosen methodology involve both subjective and informed qualitative evaluation without the use of environmental indices, which are found wanting as measures of quality. Post-multiplication of the matrices produces ranking of planning and design generators in order of importance, which, effectively, represents the choice of the urban dweller. The methodology is operationalised to test the matrix and post-multiplication procedures, and the rationality of the result. For the case model presented, a rational result was obtained, which supports the adaptation of the methodology for creative purposes. The ranking is referred to a source book, which allows the systematic transformation of the primary planning and design generators into recognisable and conventional planning directives. As a contribution to the planning and design fields, the methodology is a useful creative tool, effectively addressing the problem of the interface between planner and user in the attainment of spatial quality in the development of new urban settings. Furthermore, the procedures can be operationalised to meet an infinite range of variables, or spatial scenarios within the urban setting.